Unprecedented rainfall over Bangalore city during October, 2005 - MOHAPATRA, M.; KUMAR , NARESH; BANDYOPADHYAY, B. K. (MAUSAM, 2010)
The Central Observatory of India Meteorological Department (IMD) at Palace Road, Bangalore reported a record highest monthly rainfall of 604 mm during October, 2005. It was the highest ever monthly rainfall recorded over Bangalore city. However, the surrounding stations in Bangalore district recorded less rainfall. To find out the physical processes leading to this rainfall, the characteristics of rainfall over different stations in Bangalore urban and rural districts during October, 2005 and associated synoptic and thermodynamic features during the month are analysed. The Urban Heat Island (UHI) effect and role of pollution parameters and their relationship with this rainfall have also been analysed. This study can be utilized in better understanding of the impact of urbanization and pollution on rainfall, especially heavy rainfall. It can also help in predicting the heavy rainfall events over the urban centres. The study endorses the earlier finding that the UHI effect leads to moisture convergence and pollutants may work as hygroscopic nuclei over the region to enhance rainfall near the urban centre.